A versatile stereocontrolled synthesis of 2-deoxyiminosugar C-glycosides and their evaluation as glycosidase inhibitors. Issue 5 (11th January 2021) - Lumbroso, Alexandre; Berthonneau, Clément; Beaudet, Isabelle; Quintard, Jean-Paul; Planchat, Aurélien; García-Moreno, M. Isabel; Ortiz Mellet, Carmen; Le Grognec, Erwan
Abstract : Dihydroxylation of (R, S) or (S, S) -2, 6-disubstituted dehydropiperidines enantioselectively obtained from stannylated precursors allows a versatile preparation of 2-deoxyiminosugar C -glycosides which have been evaluated as glycosidases inhibitors. Abstract : A highly enantioselective synthesis of ( R, S ) or ( S, S )-2, 6-disubstituted dehydropiperidines has been previously achieved through Sn/Li transmetalation of the corresponding stannylated dehydropiperidines or of their precursors. Herein, we successively consider their Upjohn's syn dihydroxylation and their anti -dihydroxylation via an epoxidation reaction followed by epoxide opening reaction. The stereochemical course of these reactions was first reported including the use of appropriate protecting groups before considering the conversion of the obtained compounds into NH or NMe iminosugar hydrochlorides. A primary evaluation of the designed iminosugar C -glycosides as glycosidase inhibitors suggests candidates for the selective inhibition of α-galactosidase, amyloglycosidase and naringinase. Beyond the reported results, the method constitutes a highly modulable route for the synthesis of well stereodefined iminosugar C -glycosides, an advantage which might be used for the design of iminosugars to enhance their biological properties.